Quantitative Micro-Complement Fixation Test - Marucci, A. A. (1971)
A quantitative micro-complement fixation test capable of detecting nanogram quantities of antigen is described. The test is simple to perform and is highly reproducible. Typical results from three antigen-antibody systems are given.